2012
DOI: 10.1002/mds.25115
|View full text |Cite
|
Sign up to set email alerts
|

Multiple system atrophy–parkinsonism with slow progression and prolonged survival: A diagnostic catch

Abstract: Late appearance of dysautonomia is a favorable prognostic factor in MSA-P. Greater awareness of this uncommon "benign" subgroup of MSA will improve diagnostic accuracy and help to more accurately inform treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 31 publications
5
69
0
Order By: Relevance
“…In MSA, OH whose estimated prevalence is 75% [1] may occur early in the disease course or late as in long-surviving patients [7,8]. In PD a recent meta-analysis reported a 30% prevalence at any stage of the disease with a large statistical heterogeneity between studies [9].…”
Section: Introductionmentioning
confidence: 95%
“…In MSA, OH whose estimated prevalence is 75% [1] may occur early in the disease course or late as in long-surviving patients [7,8]. In PD a recent meta-analysis reported a 30% prevalence at any stage of the disease with a large statistical heterogeneity between studies [9].…”
Section: Introductionmentioning
confidence: 95%
“…Traditionally, standard dopaminergic therapy for treatment of Parkinson's disease was thought to provide only minimal improvement in symptoms induced by MSA, as reflected in diagnostic criteria for probable MSA-P [1] . Previous studies have reported survival between 6 and 9 years among MSA patients [3,4,15] , although longer survival (>15 years from symptom onset) has been described in definite MSA-P cases [20] . In the above EMSA study [18] and the US cohort [19] , the overall survival was around 10 years; however, our study indicated an even worse prognosis.…”
Section: Previous Evidencementioning
confidence: 99%
“…OH may occur early in the course of the disease, and in these cases is associated with a shorter survival time [10,11]. Similarly, recent studies demonstrated that in long-surviving patients, cardiovascular dysautonomia occurred late in the disease course suggesting that late onset of cardiovascular AF in MSA patients may be a favorable prognostic factor [12,13]. …”
Section: Clinical Observationmentioning
confidence: 99%